Handbook of microelectromechanical systems - Versuh, Eve (NY Research Press, 2015)
This is an all-inclusive book on microelectromechanical systems (MEMS). The developments of MEMS and devices have been influential in the demonstration of new devices and techniques, and even in the influx of new fields of research and developments such as BioMEMS, actuators, microfluidic devices, RF and optical MEMS. Therefore, the need is for MEMS book which incorporates the recent advances in the field. This book is prepared by the specialists in the field of MEMS. It consists of two major sections dedicated to RF and Optical MEMS, and MEMS based Actuators.